Establishing (177)Lu-PSMA-617 Radioligand Therapy in a Syngeneic Model of Murine Prostate Cancer - Fendler, Wolfgang P. (J Nucl Med, 2017)
Clinical (177)Lu-PSMA-617 radioligand therapy (RLT) is applied in advanced-stage prostate cancer. However, to the best of our knowledge murine models to study the biologic effects of various activity levels have not been established. The aim of this study was to optimize specific and total activity for (177)Lu-PSMA-617 RLT in a syngeneic model of murine prostate cancer. Methods: Murine-reconstituted, oncogene-driven prostate cancer cells (0.1 × 10(6)) (RM1), transduced to express human prostate-specific membrane antigen (PSMA), were injected into the left flank of C57Bl6 immunocompetent mice. RLT was performed by administering a single tail vein injection of (177)Lu-PSMA-617 at different formulations for specific (60 MBq at high, 62 MBq/nmol; intermediate, 31 MBq/nmol; or low 15 MBq/nmol specific activity) or total activity (30, 60, or 120 MBq). Organ distribution was determined by ex vivo γ-counter measurement. DNA double-strand breaks were measured using anti–gamma-H2A.X (phospho S139) immunohistochemistry. Efficacy was assessed by serial CT tumor volumetry and (18)F-FDG PET metabolic volume. Toxicity was evaluated 4 wk after the start of RLT. Results: Mean tumor-to-kidney ratios ± SEM were 19 ± 5, 10 ± 5, and 2 ± 0 for high, intermediate, and low (each n = 3) specific activity, respectively. Four of 6 (67%) mice treated with intermediate or high specific activity and none of 6 (0%) mice treated with low specific activity or formulation demonstrated significant DNA double-strand breaks (≥5% γ-H2A.X–positive cells). High when compared with intermediate or low specific activity resulted in a lower mean ± SEM tumor load by histopathology (vital tissue, 4 ± 2 vs. 8 ± 3 mm(2); n = 3 vs. 6), day-4 (18)F-FDG PET (metabolic volume, 87 ± 23 vs. 118 ± 14 mm(3); n = 6 vs. 12), and day-7 CT (volume, 323 ± 122 vs. 590 ± 46 mm(3); n = 3 vs. 6; P = 0.039). (177)Lu-PSMA-617 (120 MBq) with high specific activity induced superior tumor growth inhibition (P = 0.021, n = 5/group) without subacute hematologic toxicity (n = 3/group). Conclusion: (177)Lu-PSMA-617 (120 MBq) and high specific activity resulted in the highest efficacy in a syngeneic model of murine prostate cancer. The model will be useful for studying the effects of PSMA-directed RLT combined with potentially synergistic pharmacologic approaches.